Evaluation of the Management Information System at the Primary Health Care in the National Health Insurance Program in Surakarta - Astri Sri Wariyanti; Arief Suryono; Dono Indarto Indarto (Journal of Health Policy and Management, 2016)
Background: Management information system are intended to facilitate National Health Insurance (BPJS Kesehatan). This study aimed to evaluate the evaluation of the management information system so-called Primary Care (PCare) at the primary health care in the national health insurance program in Surakarta, Central Java.Subjects and Methods: This was a descriptive-qualitative study. This was carried out in four selected community health center in Surakarta in August-November 2016. The data was collected with observation and in-depth interviews, documentation and triangulation. The data was analyzed by data reduction,data presentation, and conclusion.Results: The application of PCare in Surakarta facilitated patient service. But there were some obstacle and error in the implementation of Pcare.Conclusion: Pcare in Surakarta does not run optimally. But PCare facilitate service to patients and reporting system at BPJS Surakarta.Keywords: information systems, community health centers, primary care social and health care security in community health center.Correspondence:Astri Sri Wariyanti. School of Health and Sciences, STIKes Mitra Husada, Karanganyar, Surakarta. Email: astri_new89@yahoo.comJournal of Health Policy and Management (2016), 1(1): 53-60https://doi.org/10.26911/thejhpm.2016.01.01.08